Teesside coronary survey: an epidemiological study of acute attacks of myocardial infarction. Issue 6045 (13th November 1976) - Colling, A; Dellipiani, A W; Donaldson, R J; MacCormack, P
Abstract : A 12-month epidemiological survey of attacks of acute myocardial infarction was carried out in a large urban population. The incidence and mortality at all ages and in both sexes were examined. Altogether, 1938 attacks were diagnosed--an overall incidence of 4-89 per 1000 population. The 28-day fatality rate was 50-5%. A third of the patients were treated at home and these patients had a lower fatality rate than those in hospital, a difference that could not be attributed to age, sex, or severity of attack. Half of the deaths that were witnessed occurred suddenly and a further 21% occurred within the next two hours. The median time to patients coming under care was about three hours. As used at present, coronary care units are unlikely to improve fatality rates. Future advances in treatment must take place outside hospital and will require re-education of the public and the general practitioner.